Odpowiedź:
[tex]5x\\\\x=1\ \ \ \ \ \ \ \ 5x=5\cdot1=5\\\\x=0\ \ \ \ \ \ \ \ \ 5x=5\cdot0=0\\\\x=-1\ \ \ \ \ \ 5x=5\cdot(-1)=-5\\\\\\2x-4\\\\x=1\ \ \ \ \ \ \ \ 2x-4=2\cdot1-4=2-4=-2\\\\x=0\ \ \ \ \ \ \ \ 2x-4=2\cdot0-4=0-4=-4\\\\x=-1\ \ \ \ \ \ 2x-4=2\cdot(-1)-4=-2-4=-6\\\\\\x(x-1)\\\\x=1\ \ \ \ \ \ x(x-1)=1\cdot(1-1)=1\cdot0=0\\\\x=0\ \ \ \ \ \ x(x-1)=0\cdot(0-1)=0\cdot(-1)=0\\\\x=-1\ \ \ \ \ \ x(x-1)=-1\cdot(-1-1)=-1\cdot(-2)=2[/tex]
[tex]4-x\\\\x=1\ \ \ \ \ \ \ \ 4-x=4-1=3\\\\x=0\ \ \ \ \ \ \ \ 4-x=4-0=4\\\\x=-1\ \ \ \ \ \ 4-x=4-(-1)=4+1=5[/tex]